Pengaruh Kualitas Air Rumah Tangga Terhadap Kejadian Diare Pada Anak Balita Di Daerah Padat Penduduk Perkotaan - Sudrisman (Jurnal Ilmu Kesehatan Terpadu Indonesia, 2025)
Diarrhea in children under five is a significant public health issue, particularly in densely populated urban areas. This study aims to analyze the effect of household water quality on the incidence of diarrhea among children under five. A cross-sectional design was applied with 120 children aged 0–59 months as the sample. Data were collected through interviews, household sanitation observations, and water sample analysis for microbiological, physical, and chemical parameters. Data were analyzed using descriptive statistics, Chi-square tests, and logistic regression. The results indicated that 35% of children experienced diarrhea, and E. coli contamination in household water increased the risk of diarrhea by 3.2 times. Open water storage also increased the risk by 2.1 times. Household sanitation and handwashing behavior had a smaller but notable influence. The study emphasizes the importance of improving household water quality, proper water treatment and storage, and hygiene education to reduce diarrhea incidence among children under five.